On the Effect of Silicon Substitution in Na3V2(PO4)3 on the Electrochemical Behavior as Cathode for Sodium‐Ion Batteries. Issue 2 (15th November 2017) - Aragón, María J.; Lavela, Pedro; Ortiz, Gregorio F.; Alcántara, Ricardo; Tirado, José L.
Abstract: A new Na3+ x V2 (PO4 )3− x (SiO4 ) x (0≤ x ≤0.5) series is examined as the positive electrodes for sodium‐ion cells. The substitution of P by Si is evidenced by an increase in the lattice parameters and a significant modification of the particle morphology. These structural and morphological changes significantly affect the electrochemical performance. Thus, samples with low Si contents reveal better rate capabilities and cyclabilities than the Si‐free sample. A full ion cell assembled with a selected sample provides an energy density of 342 W h kg −1 after 140 cycles, demonstrating that Si doping on Na3 V2 (PO4 )3 could be an interesting strategy for high‐performance Na‐ion cells. Abstract : Be positive : Phosphosilicates in sodium‐ion cells can offer a good strategy to improve cell performance. A new Na3+ x V2 (PO4 )3− x (SiO4 ) x series reveals appropriated structural and morphological changes, favoring ion diffusion and, hence, the rate capability and cyclability of sodium cells assembled with these materials as positive electrodes.